Abu Ishaq Al-Syathibi and His Perspective on Maslahat - Ikhsan, Muhammad; Iskandar, Azwar (Universitas Nurul Jadid, 2021)
This study aims to find out: (i) the position of Abu Ishaq al-Syathibi as a fiqh scholar al-maqāṣid; and (ii) the concept of maslahat in the perspective of Abu Isha al-Syathibi. This research is qualitative descriptive research with library research techniques through historical and sociological approach. The results found that al-Syathibi's ability as a reformer in the realm of uṣūl al-fiqh was very clear in his role in performing new formulations of the theory of al-maqāṣid and managed to open the views of the scholars afterwards to further examine this issue. Al-Shatibi's view of maslahat cannot be separated from his view of al-maqāṣid, especially when he divides the al-maqāṣid into two major parts: those relating to maqāṣid al-syarī'ah and those relating to maqāṣid al-mukallafīn.